Heritage Tram Lines in Wrocław: analysis of the tourist offer from an urban tourism perspective - Kołodziejczyk, Krzysztof (Turyzm/Tourism, 2019)
The aim of the article is to assess the operation of Heritage Tram Lines in Wrocław in 2018 in terms of the attractiveness of the offer for tourists, uptake, the costs of its maintenance and profitability, to finally indicate some general conclusions on this urban tourism offer. The present moment is special as an increase in carriers (transport companies) operating the Lines from one to two has enabled various changes to be made. Based on data on the number of tickets being sold it is possible to assess that the Lines are most popular in July and August, however even then statistically less than half of the seating places are occupied. Trips with a guide are less frequented than rides without. As a consequence, in this article several suggestions are presented which may help the Lines become more popular: for example a longer period of operation (in a day and in a year), the introduction of new ticket types and additional attractions.